2013
DOI: 10.1007/s12562-013-0644-3
|View full text |Cite
|
Sign up to set email alerts
|

Synergy of microcapsule polysaccharides and Bacillus subtilis on the growth, immunity and resistance of sea cucumber Apostichopus japonicus against Vibrio splendidus infection

Abstract: A 4-week feeding trial was conducted to determine the effects of different dietary supplements on the growth, immunity and resistance of sea cucumber Apostichopus japonicus against Vibrio splendidus infection. The control group was supplied with blank microcapsules, and Astragalus polysaccharide (APS) microcapsules, tuckahoe polysaccharide (TPS) microcapsules, (APS ? TPS) microcapsules, (APS ? TPS) microcapsules ? Bacillus subtilis, were tested for effects. Coelomic fluid was collected at 7-day intervals to te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 43 publications
2
9
0
Order By: Relevance
“…Comparing E 1 and E 2 , the highest values for final weight and SGR and the lowest for FCR were in the E 2 treatment, which indicates that APS enhanced the effect of probiotics for growth performance (Table 1) by promoting the absorption and utilization of nutrients as an adjuvant. This result was similar to that of Fan et al (2013) and Zhang et al (2010); Fan et al (2013) showed that APS and tuckahoe polysaccharides (TPS) enhanced the effect of Bacillus subtilis on the growth, immunity, and resistance of Apostichopus japonicas while Zhang et al (2010) found that fructo‐oligosaccharides and B. subtilis exerted a synergistic effect on enhancing the immunity and disease resistance of sea cucumbers. The CP, CF, CA, and moisture content of fish in the E 2 treatment varied compared to those in the C 0 treatment (Table 2).…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…Comparing E 1 and E 2 , the highest values for final weight and SGR and the lowest for FCR were in the E 2 treatment, which indicates that APS enhanced the effect of probiotics for growth performance (Table 1) by promoting the absorption and utilization of nutrients as an adjuvant. This result was similar to that of Fan et al (2013) and Zhang et al (2010); Fan et al (2013) showed that APS and tuckahoe polysaccharides (TPS) enhanced the effect of Bacillus subtilis on the growth, immunity, and resistance of Apostichopus japonicas while Zhang et al (2010) found that fructo‐oligosaccharides and B. subtilis exerted a synergistic effect on enhancing the immunity and disease resistance of sea cucumbers. The CP, CF, CA, and moisture content of fish in the E 2 treatment varied compared to those in the C 0 treatment (Table 2).…”
Section: Discussionsupporting
confidence: 87%
“…Similarly, the enhanced activities of the antioxidant enzymes have been demonstrated in the serum of Nile tilapia (Abarike et al, 2018) and common carp (Wang et al, 2017) that were fed a mixture of B. subtilis and Bacillus licheniformis . However, it was reported that polysaccharides from various traditional Chinese herbs exert an immune response both in vivo and in vitro (Ando et al, 2002; Bedir et al, 2000; Cui et al, 2003; Fan et al, 2013). In our study, the polysaccharides could have optimally eliminated ROS to maintain homeostatic balance, which is why higher enzyme activities were detected.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…2012; Keysami & Mohammadpour 2013; Fan et al . 2013a). Besides, several other Bacillus species such as Bacillus aryabhattai (Tepaamorndech et al .…”
Section: Bacillus Group Of Probiotics With Reference To Bacillus Subtmentioning
confidence: 99%